Review of the Great Book ’AA Lamul Fuqaha Wal Muhaddeseen’ - Rahman, M Shafique (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v3i0.2686 IIUC STUDIES Vol. - 3, December 2006 (p 199-202)